(ØÙƒÙ… "Ø¨ÙŠÙ„ÙŠØ³" ÙÙŠ Ø§Ù„Ø²ÙˆØ§Ø¬ Ø§Ù„Ø¹Ø±ÙÙŠ ÙÙ‰ Ù‚Ø¨ÙŠÙ„Ø© "Ù„Ø§Ù…Ø§ØÙˆÙ„ÙˆØ·" ÙÙ‰ Ù…Ø¯ÙŠÙ†Ø© "Ù„Ø§Ø±Ø§Ù†ØªÙˆÙƒ" Ø¨ÙÙˆÙ„ÙˆØ±ÙŠØ³ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© Ù†ÙˆØ³Ù‰ ØªÙ†Ø¬Ø±Ø§ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ù†Ù‚Ø¯ÙŠØ© - Sulaiman, Umar; Berkah, Dian; Basith, Abdul (Maqasid: Jurnal Studi Hukum Islam, 2020)
Abstract In the life of the Lamaholot tribe, customs and beliefs are still developing strongly. It is still found in the Lamaholot tribal community in East Flores, East Nusa Tenggara regarding "Belis" in the marriage process. "Belis" is a tradition of noble values and forms of respect for women. The purpose of "Belis" is the legal determinant of a marriage, as a sign that the girl has left her home family, and as a tool to raise the name / degree of the family There are various forms of "Belis" in East Nusa Tenggara that are used in the form of gold, silver, money, and animals such as buffalo, cows or horses. The uniqueness of the "Belis" lamaholot community is concrete in the form of value and size of elephant ivory that is difficult to obtain. Although elephant ivory is very difficult to obtain, this tradition still applies and is maintained by the Lamaholot community.The purpose of this study is 1) to find out how the traditional practice of "Belis" in the Lamaholot tribe community 2) to find out how the views of ulama, traditional leaders, and the viewpoint of Islamic law about the customs. The subjects of this research are the local community, community leaders and Ulama '. This research is a type of qualitative research using data collection methods and methods of observation, interviews, and documentation while the data processing is Editing, Classifying, Analizing and Concluding.The conclusions of this study are 1) that the tradition of "Belis" in the Lamaholot tribe is a legacy of ancestors and until now this tradition still exists 2) according to traditional leaders and different religious leaders, according to religious leaders that the tradition of "Belis" is contrary to the Shari'a Islam. And according to traditional leaders, adat belis does not contradict because adat has to be maintained. But to maintain the brotherhood between them, they are at peace and agree to improve the custom of "Belis". If viewed from the perspective of Islamic law that part of the traditional process of "Belis" is contrary to the basic method of Islamic law. Keywords: Belis, Tradition, Marriage